ANALISIS NILAI SOSIAL DALAM CERITA RAKYAT TANJUNG PAMALI KECAMATAN WABULA KABUPATEN BUTON - Muslim, Muslim ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2022)
Community groups that have a culture produce literary works as a result of their members' thoughts and comments on that culture. Folklore exhibits various linguistic behaviors that reflect societal norms. This study uses a qualitative descriptive methodology presented from the Tanjung Pamali folklore and is used in this study as data on social values. Qualitative research that produces descriptive information about a person, condition, or symptom of a particular group that is observed in the form of written or spoken words. The findings reveal the following as integral components of the folklore of Tanjung Pamali, Wabula District, and Buton District: The main themes of folklore are: (1) the struggle of a mother during childbirth; (2) the search for true love; and (3) the effect of inbreeding. The Tanjung Pamali folklore is an advanced plot. The characters in this folklore are Wa Kaakaa, Wa Bulabula, Sri Bajala Hoku Lasiaka, Piramasuni, La Sarongarea, and La Kampue. The social values ​​considered include the importance of caring for one another, acting bravely, the effect of inbreeding, the value of devotion and the importance of dedication.